Data analytics to allocate berths in reserved compartments in Indian railways - S. Satyanarayana, M; D.C, Abhilash; G, Srinivasa (International Journal of Engineering and Technology, 2018)
Indian Railways is one of the biggest nationalized organization in India. Started in the year 1832 for goods carriage and 1853 for passengers [1]. Indian Railways is 4th biggest railway zone amongst all in the world after USA, China and Russia. Indian railways operating their services in India by providing their services by laying the track of 67,368 KMâ€™s. And the services are improvised day by day like from Narrow Gauge to Brad Gauge, Single Track to Double and Triple Tracks, Electrification of lines etc.., though the Indian Railways are improving day by day the facilities in different sectors, still there are some areas where the traditional ways are followed by Indian Railways likely while booking tickets in reserved compartments, Railway Gates etc [1], In this research paper, the main aim is to develop an analytical system to allocate berths in the reserved coaches based on the architecture and facilities available in the coaches. Existing way of allocating berths in the reserved coaches is not sufficient to serve the needy, though they reserved their seats on their own. In this paper the new way of allocating berths is been defined to serve the needy by using Big Data Analytics. The analytics are performed in both Normal Reservation Coaches and Air-Conditioned coaches and improvises the profit by increasing the number of passengers travelling in Indian railways every year.Â Â
Keywords: Indian Railways Reserved Coaches; Big Data Analytics; Passengers; Allocating Berths.